(untitled) (Journal of Partial Differential Equations, 1992)
In this paper, the theory of Nash point equilibria for variational functionals including the following topics: existence in convex and non-convex cases, the applications to P. D. E., and the partial regularity, is studied. In the non-convex case, for a class of functionals, it is shown that the non-trivial solutions of the related systems of Euler equations are exactly the local Nash point equilibria and the trivial solution can not be a Nash point equilibrium.